A Bioreactor for 3D In Vitro Modeling of the Mechanical Stimulation of Osteocytes - Aw Yong, Koh Meng; Horst, Eric; Neale, Dylan; Royzenblat, Sonya; Lahann, Joerg; Greineder, Colin; Weivoda, Megan; Mehta, Geeta; Keller, Evan T. (Frontiers in Bioengineering and Biotechnology, 2022)
The bone is a mechanosensitive organ that is also a common metastatic site for prostate cancer. However, the mechanism by which the tumor interacts with the bone microenvironment to further promote disease progression remains to be fully understood. This is largely due to a lack of physiological yet user-friendly models that limit our ability to perform in-depth mechanistic studies. Here we report a tunable bioreactor which facilitates the 3D culture of the osteocyte cell line, MLO-Y4, in a hydroxyapatite/tricalcium phosphate (HA/TCP) scaffold under constant fluidic shear stress and tunable hydrostatic pressure within physiological parameters. Increasing hydrostatic pressure was sufficient to induce a change in expression of several bone remodeling genes such as Dmp1, Rankl and Runx2. Furthermore, increased hydrostatic pressure induced the osteocytes to promote the differentiation of the murine macrophage cell line RAW264.7 toward osteoclast-like cells. These results demonstrate that the bioreactor recapitulates the mechanotransduction response of osteocytes to pressure including measuring their functional ability in a 3D environment. In conclusion, the bioreactor would be useful for exploring mechanisms of osteocytes in bone health and disease.